Revisiting Value-Added Tax Structures: Strategies For Mitigating Regressivity In Basic Commodities Consumption - Kartiko, Nafis Dwi; Firmansyah, Amrie (Educoretax, 2024)
This study explores the advantages and disadvantages of implementing a value-added tax on tax-exempt essential goods in Indonesia. The research employs historical, comparative, empirical, and normative legal methods to analyze the tax policy's legal and socio-economic context and assess its impacts and challenges. The analysis shows that applying VAT to necessities with exemptions can increase transparency, reduce tax avoidance, and ensure a fair distribution of the tax burden among businesses and consumers. However, this policy may impose additional administrative burdens and financial pressures on companies, particularly small and medium enterprises. It is crucial to balance promoting tax compliance and alleviating excessive administrative requirements. This research provides extensive insights into the dynamics of VAT policy on essential goods in Indonesia. It presents new perspectives on the distribution of economic burden and provides recommendations based on thorough legal analysis.